Apremilast treatment of immune-mediated inflammatory skin diseases: a narrative review - Liang, Xiaoqian; Zheng, Jiecheng; Huang, Xueyi; Tan, Min; Liao, Jia (Frontiers in Pharmacology, 2025)
Novel therapeutic approaches on molecular pathways are being developed to treat inflammatory and autoimmune cutaneous dermatoses. Apremilast is an orally administered small-molecule phosphodiesterase 4 (PDE4) inhibitor that upregulates intracellular cyclic 3′,5′-adenosine monophosphate (cAMP) levels to mediate a large array of proinflammatory cytokines as well as exerts its anti-inflammatory functions and therapeutic efficacy in skin diseases rather than an immunosuppressive mode of action. Early-phase clinical trials have demonstrated its favorable efficacy such that the United States Food and Drug Administration (USFDA) has approved its use for the treatment of psoriasis, psoriatic arthritis, and Behçet’s syndrome. Compared to conventional immunosuppressive therapies, apremilast has better safety and tolerability profiles that significantly reduce the risk of serious adverse reactions from long-term usage. Apremilast shows easier and faster absorption even by special areas of the body, such as nails, scalp, palms and soles of feet, and genitals, along with clinically meaningful improvements. More recently, accumulating real-world evidence has revealed that it is highly effective for treating multiple immune-mediated inflammatory skin diseases in an off-label manner; it also appears to be useful either alone or as an add-on treatment against some chronic inflammatory skin disorders recalcitrant to conventional therapies. Thus, further large-scale studies and real-life trials are necessary to better elucidate its role in dermatology. The present narrative review provides an overview of apremilast as a novel therapeutic option for skin disorders, including a comprehensive look at its pharmacology, clinical efficacy, and safety profile, with the aim of enlightening clinicians on the broad applications and full potential of this small-molecule drug based on currently available evidence.